Ms. Paek, Seon Haeng (1848-May 8, 1933) and Noblesse Oblige - Knox, Kwon (Advances in Social Sciences Research Journal, 2014)
This paper discusses the life of Ms. Paek, Seon Haeng who was a widow and a rich woman in the Japanese colonized period. Her whole life was noble and influential in Korean modern history. On May 13, 1933 there was a crowd of more than 150 000 people at the riverside of Taedong River. They were in the funeral procession of Pyongyang in memory of Ms. Paek, Seon Haeng who had devoted her whole life to loftiness. She had donated all her wealth to national education. This essay reviews the patriotic life of Ms. Paek, Seon Haeng under the colonial rule of Japanese imperialism to highlight the value of life dedicated to national education. With a view in avoiding the difference in the interpretation of the North and South Korea’s history. I have made reference mainly to the daily news of Dong-a-ilbo (1925-1933) as primary sources. In the first chapter, I dealt with Ms. Paek, Seon Haeng’s life and trials in her early years and in the next her first charity for building ‘Paekseon Bridge’. In the chapter 3, I wrote about her devotion to education. Ms. Paek, Seon Haeng’s devotion to education was originated from her anti-Japanese, patriotic inclination. She made donations to private schools, which then served as a base for national education. This reflects her anti-Japanese, patriotic mindset. In the chapter 4, I dealt with “Paek, Seon Haeng Memorial Hall” and Her Patriotism. The noble life of Ms, Paek Seon Haeng is recorded in history because her life was a laudable one, and became rich braving through all poverty and trials in her widowed life and rendered devoted service to the nation and her country. How one has earned his or her money is important; however, how one has spends his or her money is much more important. .In conclusion, Ms, Paek Seon Haeng is a representative woman who lived like a nobles oblige in the Korean modern history. I hope this essay will contribute to spotlighting the Noblesse Oblige of Ms. Paek of Pyongyang woman who devoted her patriotic life to national education with her love for the nation and her country. Keywords: Paek, Seon Haeng, Noblesse Oblige, Pyongyang, Japan, Korea, Dong-a-ilbo